Effect of obesity on the association between ATF3 gene haplotypes and C-reactive protein level in Taiwanese - Wu, Semon; Hsu, Lung-An; Cheng, Ching-Feng; Teng, Ming-Sheng; Chou, Hsin-Hua; Lin, Heng; Chang, Pi-Yueh; Ko, Yu-Lin (Clinica chimica acta, 2011)
ATF3 has traditionally been related to various inflammatory processes. Our aim was to test the statistical association between variations in the ATF3 gene and levels of nine serum inflammatory markers, including C reactive protein (CRP), in a Taiwanese population using interaction analysis. A sample population of 604 Taiwanese subjects was enrolled. Five tagging single nucleotide polymorphisms of the ATF3 gene from the Han Chinese HapMap Database were selected and genotyped. With or without adjustment for clinical covariates, ATF3 genotypes were found to be associated with CRP levels but not with other inflammatory marker levels. Minor alleles of 2 of the 5 ATF3 SNPs were associated with decreased CRP levels predominantly in non-obese subjects (Bonferoni P=0.018, and P=0.002 for rs11571530, and rs10475, respectively). Two haplotypes inferred from the 5 SNPs, GATTA and TACCA, were also associated with increased or decreased CRP levels, respectively, in non-obese subjects (Bonferoni P=0.012 and P=0.01, respectively) but not in obese subjects. Interaction analysis revealed interaction of obesity with an ATF3 genotype associated with a high CRP level (interaction P=0.006 for SNP rs10475). An effect of obesity on CRP level was also noted in haplotype interaction analysis (interaction P=0.019 for haplotype TACCA). ATF3 polymorphisms are independently associated with CRP levels in Taiwanese subjects. Further, ATF3 genotypes/haplotypes interact with obesity to set CRP levels. These findings may have implications for the prediction of atherosclerotic disease.